Tree of heaven : poems - McKean, James, 1946 July 4- (Iowa City, IA : University of Iowa Press, 1995)
This second book by James McKean displays a large, dignified, and precise talent - McKean is always looking and reaching out to the difficult world, pulling it to him for examination. Although beginning with outward themes of travels and crossings, Tree of Heaven circles in the end to the journeys of the inner life: the struggle to understand, the ability to see, to suffer the trials of illness and death, to survive love and longing, learning when to leave things as they are, when to let go. McKean's accomplished voice is quiet but firm, at times full of wonder, exploring the personal and discovering what salvation there is in rhythm and words.
Fireflies -- Sow bear -- Teaching canaries how to sing -- Tell me -- This way, please -- The place of mosquitoes -- Whispering in Leo Kauf's ear -- The ride back -- Rowboat -- Worry dolls -- Heron -- The night before a morning's fishing -- Your leaving -- Lava flow, wahaula -- Ice -- Skin test -- Whale rock -- Les grues -- The try-your-strength machine at the Tivoli Gardens -- House wrens -- Breakneck -- Fake id -- Splitting wood -- Reunion, Cannon Beach -- A hawk in the yard -- Net -- A story after dinner -- Two magpies -- Just in case -- Snow angel -- Orchard -- Tree of heaven -- Concert -- Pelican -- In the mind's eye -- Fire line -- Silver thaw -- Driving to Multnomah Falls -- The blessing of habit -- First snow -- Quarry -- Dead reckoning -- Rider -- Hooking yourself.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
eBooks on EBSCOhost
Keywords: Poetry; American poetry; Poetry as Topic; Poésie.; Poésie américaine.; poetry; POETRY -- American -- General; American poetry; Poetry; American poetry; Poetry